Analysis of Microbiological Culture Specimens in Shree Birendra Hospital, Chhauni - Pandey, Jagat S (Medical Journal of Shree Birendra Hospital, 2003)
Analysis of Microbiological Culture Specimens in Shree Birendra Hospital, Chhauni